2011
DOI: 10.1103/physreve.84.046406
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Alfvén wave instability driven by a field-aligned current in high-βplasmas

Abstract: Including the ion-gyroradius effect, a general low-frequency kinetic dispersion equation is presented, which simultaneously takes account of a field-aligned current and temperature anisotropy in plasmas. Based on this dispersion equation, kinetic Alfvén wave (KAW) instability driven by the field-aligned current, which is carried by the field-aligned drift of electrons relative to ions at a drift velocity V(D), is investigated in a high-β plasma, where β is the kinetic-to-magnetic pressure ratio in the plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The instability of the KAW, driven unstable by electrons drifting parallel to the magnetic field with a drift velocity V d , has been investigated for a high -b (Chen et al, 2011) as well as a low -b plasma (Chen et al, 2013). In both the cases it was found that the wave growth increases with increasing drift velocities of the electrons.…”
Section: Resultsmentioning
confidence: 97%
“…The instability of the KAW, driven unstable by electrons drifting parallel to the magnetic field with a drift velocity V d , has been investigated for a high -b (Chen et al, 2011) as well as a low -b plasma (Chen et al, 2013). In both the cases it was found that the wave growth increases with increasing drift velocities of the electrons.…”
Section: Resultsmentioning
confidence: 97%
“…essentially electron beams drifting with respect to stationary ions [32] or fast ion beam excitation [33]. Chen et al [34] considered the situation when KAWs are excited by current (fluid) instability. The instability condition for this excitation by current is satisfied when the drift velocity, v D = 0.1v A , and KAWs can efficiently grow.…”
Section: Figmentioning
confidence: 99%
“…The instability condition for this excitation by current is satisfied when the drift velocity, v D = 0.1v A , and KAWs can efficiently grow. However, Chen et al [34] did not include the resonant excitation of DAWs by the inverse Landau damping because its instability condition requires a larger drift velocity, in general, larger than the Alfven velocity. Tsiklauri [7], Bian and Kontar [35] considered a different regime, where the importance of the Landau (Cerenkov) resonance for the particle acceleration and parallel electric field generation by the DAWs.…”
Section: Figmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] For example, Chen et al 19 examined the kinetic Alfv en wave instability driven by a field-aligned current in high b plasmas. Hollweg and Kaghashvili 20 examined the density fluctuations of a linearly polarized Alfv en waves in a shear flow.…”
Section: Introductionmentioning
confidence: 98%